Habitation rights of the surviving spouse or, if it’s the case, the surviving cohabiting partner - Aguilar Llanos, Benjamín (2014)
The right of habitation is the one given by the law; it consists that, after the death of the testator, the surviving spouse or the surviving cohabitant who doesn’t have   enough resources is allowed to have the house-room gratuitously and for life.In this article, the author explains some differences and similarities of the Peruvian regulation of such right of habitation compared with those existing in other Civil Codes, its necessary requirements, the possible consequences it may have on the rest of the heirs and the situations in which this right canbe applied.